2020
DOI: 10.22541/au.160315194.43095091/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impacts of anti-inflammatory phosphodiesterase inhibitors on a murine model of chronic pulmonary inflammation

Abstract: Chronic obstructive pulmonary disease (COPD) often tends to respond poorly to glucocorticoid (GC) therapy. Reduced Histone deacetylase-2 (HDAC-2) activity is an important mechanism behind this GC insensitivity. In this study, we investigated the effects of three phosphodiesterase inhibitors (PDEIs), with anti-inflammatory propensity, on cigarette smoke (CS) induced pulmonary inflammation and HDAC-2 activity. Male C57BL/6 mice were exposed to cigarette smoke (CS) over the course of 30 weeks. Administration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…The dual effect of continuous airway inflammation and decreased blood flow is continuous decreases in lung function leading to abnormal blood gas and decreased oxygenation, which aggravates the condition of the patient [8,9]. As a result of the continuous increase in immunology-related clinical research, it has been shown that immunomodulatory dysfunction contributes to the occurrence and progression of COPD with respiratory failure, and that regulation of immune function improves the condition of the patient [10]. The traditional clinical treatment of COPD with respiratory failure is based on conventional methods such as anti-inflammatory, antiinfective, and expectorant treatments to ameliorate the clinical symptoms by alleviating the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The dual effect of continuous airway inflammation and decreased blood flow is continuous decreases in lung function leading to abnormal blood gas and decreased oxygenation, which aggravates the condition of the patient [8,9]. As a result of the continuous increase in immunology-related clinical research, it has been shown that immunomodulatory dysfunction contributes to the occurrence and progression of COPD with respiratory failure, and that regulation of immune function improves the condition of the patient [10]. The traditional clinical treatment of COPD with respiratory failure is based on conventional methods such as anti-inflammatory, antiinfective, and expectorant treatments to ameliorate the clinical symptoms by alleviating the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic obstructive pulmonary disease not only have respiratory symptoms, but also involve the cardiovascular system [3], may also experience venous thromboembolism [4], and may also develop anxiety and depression. Therefore, we should pay more attention to the prevention and treatment of chronic obstructive pulmonary disease [5][6]. However, literature review studies have found that chronic obstructive pulmonary disease (COPD) has not been included in the national basic public health service projects [7], lacking policy support and community management guidelines for COPD.…”
Section: Introductionmentioning
confidence: 99%